Measuring Monetary Policy in Open Economies - Cerdeiro, Diego A. (2012)
The paper extends Bernanke and Mihov's [6] closed-economy strategy for identification of monetary policy shocks to open-economy settings, accounting for the simultaneity between interest-rate and exchange-rate innovations. The methodology allows a separate treatment of two distinct monetary policy shocks, one that operates through open market operations, and another one that takes place through interventions in the foreign exchange market. Implementation of this strategy to the case of Argentina provides the stylized facts necessary to choose among competing theoretical models of this economy. In addition to studying the effects of monetary policy innovations, the present study sheds light on the endogenous component of monetary policy. In this regard, the paper finds that, notwithstanding the relative stability of the exchange rate and the accumulation of large amounts of international reserves, the central bank in Argentina has been far from absorbing balance of payments shocks in a currency-board fashion. The growing level of international reserves can be rationalized, instead, as the monetary authority's response to terms of trade, supply and domestic currency demand shocks.